Integrated laser processing platform based on metasurface - Mingbo Pu (Opto-Electronic Advances)
Laser processing technologies enable the precise fabrication of arbitrary structures and devices with broad applications in micro-optics, micro-mechanics, and biomedicine. However, its adoption is limited by the large size, complexity, high cost, and low flexibility of optical systems. Metasurfaces enable precise multidimensional control of light fields, aligning well with the development trend toward compact, high-performance optical systems. Here, we review several recent studies on the application of metasurfaces in laser processing technologies, including 3D nanolithography, direct laser writing, and laser cutting. Metasurfaces provide an integrated operational platform with exceptional performance, poised to disrupt conventional laser processing workflows. This combination presents significant cost efficiency and substantial development potential, with promising applications in areas such as imaging, optical storage, advanced sensing, and space on-orbit manufacturing.